Reinventing (with) theory in rhetoric and writing studies: essays in honor of Sharon Crowley - Crowley, Sharon, author; Alden, Andrea, editor; Gerdes, Kendall, editor; Holiday, Judy, editor; Skinnell, Ryan, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Scholarship that takes up and extends the practices of inventive theorizing characterized by Crowley's work. Showing that theory is a continual rhetorical process that is indispensable for understanding situations and their potential significance--and a means of persuasion. Includes a foreword, afterword, and interview with Crowley.--Provided by publisher.
The fallacy of reason / Dawn Penich-Thacker -- A brief etiology of violence: the logic of identity and the metaphysics of presence / Judy Holiday -- Toward a working theory of institutional rhetorics / Ryan Skinnell -- The sophist as mentor: Sharon Crowley's rhetoric as a theory and practice of mentoring / William Lalicker, James C. McDonald, and Susan Wyche -- Reflections on being against audience with Sharon and others / Victor J. Vitanza -- Ludic rhetorics: theories of play in rhetoric and writing / Joshua Daniel-Wariya -- Unhurried conversations: writing center models for ideological intervention / Joshua C. Hilst and Rebecca Disrud -- No body is disinterested: the discursive materiality of composition in the university / Kirsti Cole -- Once more with feeling / Jennifer Lin LeMesurier -- Theory building in the rhetoric of health & medicine / J. Blake Scott and Catherine C. Gouge -- Victimless leather: toward a new materialist ethics of invention / Jason Barrett-Fox and Geoffrey Clegg -- Corporeal rhetoric as embodied action: composing in/through bodily motion / Bre Garrett -- Rhetorical futurity, or desiring theory / Kendall Gerdes -- Black religion matters: African American prophecy as a theoretical frame for rhetorical interpretation, invention, and critique / David G. Holmes -- When queers listen / Timothy Oleksiak -- Rhetoric in dimness / Matthew Heard -- Afterword: feeling and historiography / Debra Hawhee.
Keywords: English language -- Rhetoric; English language -- Rhetoric -- Study and teaching (Higher); Invention (Rhetoric); Rhetoric